Estudo geológico-estrutural e sensoriamento remoto como contribuição a hidrogeologia de terrenos cristalinos no distrito de Juá-CE - Silva, Francisco Heury Fernandes da (2007)
This research was carried out in a 130 km2 area, in the Juá village, south of the Irauçuba town. The Northeast of Brazil, specially the countryside, is marked by arid climate and irregular distribution of rain. The captation of groundwater is normally the only solution to provide water during dry weather. To minimize the natural errors that occur during the location of a well we made detailed analysis of the reptile structures that affect the Precambrian terrains. Lithologically it is constituted by igneous and metamorphic rocks belonging to the Migmatitic and Pelitic-Carbonatic Units. These rocks were reworked during the Brasilian Event, which registered both ductile and ruptile structures. In these terrains the “hydrological domain of the crystalline” is represented, in which the groundwater is controlled by ruptile structures that may be interconnected to the point of acquiring enough secondary porosity to facilitate the percolation and the storing of fluids. The structural characterization of these ruptile features was made in a detailed scale by means of the “linear-meter” technique. The remote sensing images study consisted on the application of digital processing techniques, as well as terrestrial geophysics by means of electromagnetic profiles. The structural trends obtained by satellite images are compatible with the results taken from fracturing data. The main fracture sets are N-S and E-W and secondarily, NE-SW and NW-SE. Geophysical studies revealed conductive zones related to the presence of subsurface fractures. Data integration led to two potentially important areas for hydrogeological exploration, which correspond to the C-01 (north of Juá) and C-04 (Juá) concentrations.